2020
DOI: 10.3390/pathogens9121023
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella Associated Cutaneous Lesions (BACL) in People with Neuropsychiatric Symptoms

Abstract: Bartonella species are globally important emerging pathogens that were not known to infect animals or humans in North America prior to the human immunodeficiency virus (HIV) epidemic. Ongoing improvements in diagnostic testing modalities have allowed for the discovery of Bartonella species (spp.) DNA in blood; cerebrospinal fluid; and the skin of patients with cutaneous lesions, fatigue, myalgia, and neurological symptoms. We describe Bartonella spp. test results for participants reporting neuropsychiatric sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…95 Breitschwerdt et al described 29 patients who had serological and/or PCR evidence of Bartonella infection, 24 of whom described the onset of cutaneous lesions since the onset of neuropsychiatric symptoms. 96 The majority of those lesions were similar to the striae that this patient manifested on presentation. Bartonella immunoreactivity has been detected in skin-tissue biopsies in these lesions.…”
Section: Discussionmentioning
confidence: 63%
“…95 Breitschwerdt et al described 29 patients who had serological and/or PCR evidence of Bartonella infection, 24 of whom described the onset of cutaneous lesions since the onset of neuropsychiatric symptoms. 96 The majority of those lesions were similar to the striae that this patient manifested on presentation. Bartonella immunoreactivity has been detected in skin-tissue biopsies in these lesions.…”
Section: Discussionmentioning
confidence: 63%
“…IFA antigens. Previous studies have confirmed variation in the sensitivity of IFA assays depending upon the strain type used as antigen [30,37]. In addition, and for reasons that lack clarity, a subset of patients with persistent Bartonella spp.…”
Section: Discussionmentioning
confidence: 87%
“…As all patients were diagnosed with melanoma years before study entry, and because recent studies have found Bartonella spp. bloodstream infections in healthy individuals [ 30 ], the medical relevance of the association of this genus of bacteria with melanoma awaits future studies. In addition to the small number of study participants, only two FFPE tissue blocks were retrievable, limiting documentation of tumor-associated Bartonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He was subsequently diagnosed with neurobartonellosis after he developed cutaneous lesions, which has been documented as common in individuals reporting neuropsychiatric symptoms and Bartonella spp. infection or exposure ( 10 ). He was treated with a combination of antimicrobials and experienced a gradual progressive decrease in neuropsychiatric symptoms and was able to discontinue all psychotropic drugs ( 11 ).…”
Section: Introductionmentioning
confidence: 99%